The efficacy of Hayman’s modified B - Lynch compression suture versus other surgical techniques to control atonic postpartum hemorrhage - an experience from a tertiary teaching institute - Anjan Dasgupta; Abirbhab Pal; Pradip Kumar Saha; Kamal Kumar Dash; Bivash Mondal (New Indian Journal of OBGYN)
Background: Primary postpartum hemorrhage (PPH) often encountered during caesarean sections and uterine atony itself is the single leading cause in almost 80% of cases. Recent interest on the surgical compression sutures for the treatment of massive atonic PPH has come up in the front line not only for its easy applicability, but also for its uterine salvage and future fertility preserving procedure. Aims and objectives: 1) To determine the efficacy of modified B-Lynch (Hayman’s technique) procedure over other surgical technique in managing atonic PPH; 2) To determine how this procedure obviates the need for hysterectomy in young mothers; 3) Short term maternal outcome. Methodology: This is an ethically approved hospital based prospective study, conducted at Midnapore Medical College, West Bengal, India, from January 2019 to April 2020. Atonic PPH mothers ineffective to medical management during LSCS were included as ‘study cases’ and applied either modified B-Lynch stitches (Group-A, n=100) or stepwise pelvic devascularization technique (Group B, n=100) with proper counseling and written consent prior to operation. Results: Among modified B-Lynch group (group - A), 93% cases found to be successful to control PPH; in other surgical group (group - B) 82% cases were found successful which is statistically significant (p<0.05). Those having risk factor for atony like post CS and repeat CS pregnancy (p< 0.05), multiparity (p< 0.05), prolong labor (p< 0.05), anaemia (p< 0.05) and PIH (p< 0.05) achieved statistically significant success among group - A than group - B. Other statistically significant favorable parameters that were found in modified group - A were less mean duration of operation (p <0.05), less mean intra-operative blood loss (p< 0.05), less hospital stay (p< 0.05), less first 6 hour postoperative bleeding (p<0.05), less post-operative blood product requirements (p<0.05) and less number of mothers having ICU/HDU admissions (p< 0.05). Requirement of general anesthesia found to be less among group A in comparison to group B (p < 0.05). Conclusion: Modified B-Lynch uterine compression suture can be a useful alternative to radical surgeries in primary massive atonic PPH which are unresponsive to medical management. It is safe, easier to perform, requires less expertization, less time consuming and with minimum complications. It can be performed in low resource environment and an excellent uterine salvage procedure.